Developing an electronic module based on mathematical literacy to enhance students' mathematical reasoning - Retno Marsitin; Nyamik Rahayu Sesanti (Jurnal Elemen, 2023)
This study aims to produce an e-module based on mathematical literacy with a valid, effective, and feasible problem-based learning approach to improve students' mathematical reasoning in multivariable calculus material. This research used a development method with the stages: analysis, design, development, and evaluation. The research subjects involved fifth-semester students' mathematics education department. Small group trials with 17 students and large group trials with 35 students. The research instruments included validation sheets, student worksheets, questionnaires, and mathematical reasoning ability test questions. Data collection used the results of the validation as validity, test results as effectiveness, and the results of the questionnaire as feasibility. Data analysis was descriptively and qualitatively. The research produced an e-module based on mathematical literacy with a problem-based learning approach that is valid, very effective, and very feasible for improving students' mathematical reasoning abilities in multivariable calculus material. The developed e-module has the potential for significant differences and increases mathematical reasoning abilities. In addition, e-module can be used as an alternative solution to electronic teaching.